Management of the Life Safety Provision System on Roads - AKHMADIEVA, Roza Sh.; MINNIKHANOV, Rifkat N. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The research of this problem is important as it is necessary to develop every person’s ability to identify and to prevent dangers and to secure personal safety on the road. Therefore, this article focuses on disclosing structural and substantial components of the management of the life safety provision system on roads. The major approach in this research of the problem was the comprehensive approach enabling to regard the personal life safety on the road as a purposeful system capable of self-arrangement and self-government for the safe behavior of members of the road and transport relations. The article discloses the essence of the life safety on the road; it represents its components as an integrative system; subjective factors affecting the life safety on the road are identified (length and periods of the shift of traffic control signals; expected time to cover a certain section of the trip); mental conditions and individual features of a person (state of health and mood); age peculiarities; level of theoretical and practical skills of the road user. The article also discloses the structure of an educating road environment for children; peculiarities of their education are identified.